Diseño del esquema de seguridad para la intranet de la Universidad Nacional de Loja, e implementación en el Área de la Energía, las Industrias y los Recursos Naturales no Renovables, utilizando herramientas OPEN SOURCE. - Moncayo Romero, Janneth Elizabeth (2010)
The computer security not requires alone of technological resources, but also of processes and qualified human resources and specialized, this goal is difficult to reach a constant change then it exists, since day by day they are discovered new vulnerabilities, new types of attacks and new patches that to apply to the institutional systems, transforming the operation of the security into an extremely complex task and plaintiff. The present document is on the development of the outline of computer security in the University Intranet, considering the threats of security from different perspectives to allow this way to know some risks that can affect to the institution, as well as to determine the level of maturity of the computer security with relationship to the standards, they are also presented a series of limits that the National University of Loja has to continue for the appropriate implementation of the tactical plan that intends in the present investigation.